The high priesthood by Philo and the reading by Clement of Alexandria (Circe de clásicos y modernos, 2018)
The paper traces briefly the properties of the high priest in the OT and summarizes how this figure is presented in the works by Philo. The high priest is presented in the Philonic texts with three characteristics: 1.- as a mediator (Fug. 108-115); 2.- completely sinless (Fug. 117-118; Spec. 1. 80-81); 3.- invested by the four elements (Mos. 2. 117-130; Spec.1. 84-96). Clement of Alexandria will project to Jesus Christ, a century and a half later, the symbolic features of the high priest of Israel that Philo had awarded to Moses.
Keywords: high priest; Philo; Clement; Moses; Jesus